Relationship Between Bacterial Vaginosis and Preterm Labour - رمضان لينا; نعيسه ثورة; المحمد زكريا (Latakia University Journal -Medical Sciences Series, 2020)
This search includes (144) preterm labor in the absence of any risk factor known to cause labor except for vaginal infections, and who have been admitted to the department of obstetrics and gynecology at Tishreen University Hospital in Lattakia during the study period (1/6/2018 to 1/6/2019). A dry smear was taken from the posterior diverticulum of the vagina and sent to the laboratory for implantation and bacterial sensitization. The vaginal ph was also measured using special paper, and cervical length was measured using vaginal eco. Study proves a higher rate of bacterial vaginosis among preterm labor patients in the absence of any risk factors known to cause labor ,and its bad influence on pregnancy period in a ratio of (47.18%). Study shows that the bacterial vaginal discharges culture is the golden diagnostic to detect vaginal infection in pregnant women, and it also shows the non-reliability symptoms and signs to confirm vaginal infection among pregnants. Streptococcus was the most common bacterial factor to cause bacterial vaginal infections among preterm labor patients in general at a rate of (42.64%).